THz Waves Improve Spatial Working Memory by Increasing the Activity of Glutamatergic Neurons in Mice - Lequan Song; Zhiwei He; Ji Dong; Haoyu Wang; Jing Zhang; Binwei Yao; Xinping Xu; Hui Wang; Li Zhao; Ruiyun Peng (Cells)
Terahertz (THz) waves, a novel type of radiation with quantum and electronic properties, have attracted increasing attention for their effects on the nervous system. Spatial working memory, a critical component of higher cognitive function, is coordinated by brain regions such as the infralimbic cortex (IL) region of the medial prefrontal cortex and the ventral cornu ammonis 1 (vCA1) of hippocampus. However, the regulatory effects of THz waves on spatial working memory and the underlying mechanisms remain unclear. In this study, the effects of 0.152 THz waves on glutamatergic neuronal activity and spatial working memory and the related mechanisms were investigated in cell, brain slice, and mouse models. Cellular experiments revealed that THz waves exposure for 60 min significantly increased the intrinsic excitability of primary hippocampal neurons, enhanced glutamatergic neuron activity, and upregulated the expression of molecules involved in glutamate metabolism. In brain slice experiments, THz waves markedly elevated neuronal activity, promoted synaptic plasticity, and increased glutamatergic synaptic transmission within the IL and vCA1 regions. Molecular dynamics simulations found that THz waves could inhibit the ion transport function of glutamate receptors. Moreover, Y-maze tests demonstrated that mice exposed to THz waves exhibited significantly improved spatial working memory. Multiomics analyses indicated that THz waves could induce changes in chromatin accessibility and increase the proportion of excitatory neurons. These findings suggested that exposure to 0.152 THz waves increased glutamatergic neuronal activity, promoted synaptic plasticity, and improved spatial working memory, potentially through modifications in chromatin accessibility and excitatory neuron proportions.